The Use of Sentence Types in Positive Beauty Campaign YouTube Advertisements - Efendi, Lutfi; Hardjanto, Tofan Dwi (MIMESIS, 2023)
Beauty products use social media to advertise their products to get people to know them. To attract the audience, the advertisers need to reflect the sentence types as well as the titles as the marketing approach. Understanding the sentence types essential for the company to reach the targeted market. This research studied the sentence types of positive beauty campaign YouTube advertisements. The data collecting technique is through document review by using converted spoken utterances from the positive beauty campaign YouTube advertisement videos. The encrypted videos are from Pantene Pro-V It’s time we see grey hair differently #PowerOfGrey, NEW Rare Beauty by Selena Gomez, Unilever Positive Beauty, and Dove Beauty on your own term #MyBeautyMySay. The results showed that declarative sentences are the most widely used in advertisements. Through declarative sentences, the advertisers persuade the audience to have a look at the message of the positive beauty campaign. Also, the purpose of a positive beauty campaign is to spread and embrace a positive awareness of beauty, therefore the role of the sentence type is significant to support the message of the advertisement.